El color de Virgilio - Segura Ramos, Bartolomé (Cuadernos de Filología Clásica. Estudios Latinos, 2007)
As other many aspects in his production, the colour has also been studied in Virgil. We have too been interested in the so called «psycological» as well as «aesthetic aspects» of the colour in Virgil and given to this consideration the convenient importance.